The Implementation of an Innovative Hydration Monitoring App in Care Home Settings: A Qualitative Study - Steven, Alison; Wilson, Gemma; Young-Murphy, Lesley (JMIR Publications, 2019)
BackgroundIn response to marked concern regarding inadequate fluid intake recording in care homes, an innovative mobile hydration app was collaboratively developed. "Hydr8" aimed to facilitate accurate recording and communication of residents' fluid intake and ultimately increase care quality and patient safety. ObjectiveThe aim of this study was to examine the implementation of Hydr8 in a sample of care homes in one area in England. MethodsThe principles of Realist Evaluation and Action research were drawn upon throughout the study. Overall, 5 care homes participated in this study, 3 interview-only sites and 2 case-study sites, where interviews and observations were conducted at 3 time-points. Furthermore, 28 staff members participated, including care staff, management, a registered nurse, and administrative staff. ResultsFindings suggest that Hydr8 benefits practice, enhancing the understanding of hydration and person-centered care and improving staff communication. However, technical glitches hindered the seamless embedding of Hydr8 into everyday practice, and enthusiasm for long-term use was dependent on the resolution of issues. In addition, Hydr8 heightened perceptions of personal accountability, and while managers viewed this as positive, some staff members were apprehensive. However, individuals were enthusiastic about the long-term use and potential of Hydr8. ConclusionsUtilizing the findings of this study to further develop and adapt Hydr8 indicates the long-term use of Hydr8 as promising. Although perceptions of Hydr8 were primarily positive, setbacks in its implementation and use created difficulties in normalizing the solution into everyday practice. This study highlights the need for education related to hydration practice and a change of infrastructure in care home settings to implement technical solutions and changes to care.